A Qualitative Examination of the Role of Small, Rural Worksites in Obesity Prevention - Escoffery, Cam (Centers for Disease Control and Prevention, 2011)
INTRODUCTION: The prevalence of overweight and obesity in the United States is highest in rural counties. We explored social support, policies, and programmatic resources that encourage more healthful diets and participation in physical activity among employees of small, rural worksites. METHODS: We conducted in-depth interviews with 33 employed adults aged 50 years or older in rural Georgia about access to healthful foods and opportunities for physical activity at work; conversations about exercise, weight loss, and eating healthfully in general; and worksite nutrition and physical activity programs; and we asked for suggestions for making the worksite more healthful. The research team developed a codebook, and 2 coders coded each transcript. Data were analyzed and reports were generated for thematic analyses. RESULTS: Participants from rural worksites, most with fewer than 50 employees, cited lack of vending machines and cafeterias, health promotion programs to address healthful eating and exercise, and facilities for physical activity as barriers to eating healthfully and engaging in physical activity at work. Many participants reported conversations with coworkers about how to eat more healthfully by making more nutritious choices or preparing food more healthfully. Participants also discussed the importance of engaging in physical activity on their own and gave suggestions on ways to incorporate exercise into their routines. Participants' access to healthful foods at work varied, but barriers such as being too busy, worksite location, and no worksite cafeteria were noted. Some workers reported engaging in physical activity at work, and others reported a heavy workload and lack of time as barriers. CONCLUSION: Building on the social environment and implementing policies for healthful eating and participation in physical activity may help address obesity prevention in rural workplaces.